Efficacy of Topical 5% Dapsone Gel versus 0.1% Adapalene Gel in The Treatment of Mild to Moderate Acne Vulgaris - Zonia Ali; Tahir Kamal; Hina Manzoor; Ayesha Wahid; Hafsa Hafeez (Medical Journal of South Punjab, 2024)
Objective: To compare the effectiveness of topical 5% Dapsone gel and Adapalene gel 0.1% in the treatment of mild to moderate acne vulgaris.Methodology: A randomized controlled trial was conducted at Department of Dermatology, Lahore General Hospital, Lahore from 16-12-2023 to 15-06-2024. Total 60 patients were selected. The diagnosis of acne vulgaris was made by consultant dermatologist. Informed consent was taken from each patient and discretion of the information was ensured. Local and global GAGS score was calculated. Patients were separated into two groups for Dapsone 5% and Adapalene 0.1% and advised to apply their treatment gel twice daily. At fourth visit GAGS score and efficacy of the treatment were documented. Results: In group A, 80% had mild and 20% had moderate acne while in group B, 70% had mild and 30% had moderately severe acne (p=0.371). Treatment was successful in 86.7% of group A and 56.7% of group B patients (p=0.010).Conclusion: According to this study, there was significant difference between the efficacy of topical 5% Dapsone gel and topical 0.1% Adapalene gel to treat the acne in selected population and dapsone gel can be recommended as a standard treatment for acne vulgaris.